43-d=d+9

Simple and best practice solution for 43-d=d+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43-d=d+9 equation:


Simplifying
43 + -1d = d + 9

Reorder the terms:
43 + -1d = 9 + d

Solving
43 + -1d = 9 + d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
43 + -1d + -1d = 9 + d + -1d

Combine like terms: -1d + -1d = -2d
43 + -2d = 9 + d + -1d

Combine like terms: d + -1d = 0
43 + -2d = 9 + 0
43 + -2d = 9

Add '-43' to each side of the equation.
43 + -43 + -2d = 9 + -43

Combine like terms: 43 + -43 = 0
0 + -2d = 9 + -43
-2d = 9 + -43

Combine like terms: 9 + -43 = -34
-2d = -34

Divide each side by '-2'.
d = 17

Simplifying
d = 17

See similar equations:

| (x-10)=45 | | 2m+18= | | 1x+2x= | | 3x+6+x=41 | | 4.5-1.9m=20 | | 9x-2=7x-4 | | 4(7m+2)=50 | | 2/5(3x+4)=2(3-3x)+10 | | 55.7+b=32.119 | | 2x+2(x+.06)=9.6 | | k+5-k=5 | | 6w+4=-2+6w | | 4b-12=6 | | 2(6y+2)=-(-8-7y)+8y | | 18x+4x= | | 10f+17=67 | | g(4g-5)=0 | | (2x+10)=60 | | 5-7x=30-14x | | -4(1-2x)=20 | | (2x+10)= | | 8(z-5)+12=0 | | 19=-4c-1 | | 11y^2-121y= | | (5x-6)(x-1)-(2x-5x+3)=0 | | (6-5i)(3+2i)=0 | | (7-4i)+(3-i)= | | t(t-2)=0 | | 7(y-3)=4y+2 | | (2-7i)-(5-3i)= | | 2x+4=2(x-1) | | 5.75k+4.50(5-k)=5.25(5) |

Equations solver categories